Nitrogen-Doped microporous carbons derived from azobenzene and nitrile-functionalized polybenzoxazines for CO2 uptake. (September 2020) - Mohamed, Mohamed Gamal; Tsai, Mei-Yin; Su, Wei-Chen; EL-Mahdy, Ahmed F.M.; Wang, Chih-Feng; Huang, Chih-Feng; Dai, Lizong; Chen, Tao; Kuo, Shiao-Wei
Graphical abstract: Highlights: Two BZAPh and BZACN monomers were successfully prepared through Mannich condensation reaction. Poly(BZAPh)-A and poly(BZACN)-A microporous materials display high specific surface area and high char yield. Poly(BZACN)-A microporous material from azobenzene and nitrile-functionalized BZ suitable for capturing CO2 . Abstract: In this study we synthesized two nitrogen-doped microporous carbons (NMCs) from the benzoxazine monomers BZAPh and BZACN through a process of curing polymerization, calcination, and KOH activation. We prepared the benzoxazine monomers BZAPh and BZACN in high yield and purity through Mannich reactions of 1, 3, 5-tris(4-aminophenoxy)benzene (TriPh-3NH2 ), paraformaldehyde, and 4-phenylazophenol and 4-[(4-hydroxyphenyl)diazenyl] benzonitrile, respectively, in 1, 4-dioxane. We employed differential scanning calorimetry (DSC), temperature-dependent Fourier transform infrared (FTIR) spectroscopy, and thermogravimetric analysis (TGA) to characterize the ring opening polymerization and thermal stability of the uncured monomers BZAPh and BZACN and the products of their thermal treatment at various temperatures. In addition, we used TGA, wide-angle X-ray diffraction (XRD), Raman and X-ray photoelectron spectroscopies (XPS), transmission electron microscopy (TEM), and Brunauer–Emmett–Teller (BET) analyses to examine the surface areas, porous structures, surface morphologies, chemical compositions, and thermal stabilities of these two highly N-doped NMCs. The NMC derived from the BZACN monomer, possessing both azobenzene and nitrile functionalities, exhibited superior thermal properties and CO2 capture ability because it contained a high crosslinking density of the triazine functional groups after thermal curing.